2012
DOI: 10.1590/s0102-05362012000400026
|View full text |Cite
|
Sign up to set email alerts
|

Production of cocona and jurubeba seedlings in different types of containers

Abstract: The effect of different containers was evaluated to produce cocona seedlings (Solanum sessiliflorum) and jurubeba (Solanum paniculatum). The experiment was performed in the mesoregion of Alto Solimões, in Benjamin Constant, Amazonas state, Brazil, in a particular production area. The seeding was done in black holed polyethylene bags and polystyrene trays with 128, 200 and 288 cells with volumes of 250.00; 32.61; 21.60 and 9.88 cm³, respectively. We adopted a completely randomized design with four containers, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
3
2
0
4
Order By: Relevance
“…Similar results were observed by Guimarães et al (2012), working with jurubeba (Solanum paniculatum) and cocona (Solanum sessiliflorum Dunal) seedlings, which observed with a higher length, fresh and dry shoot weight for seedlings grown in containers with a larger volume (32.61, 40 and 250 cm 3 ) and consequently with more substrate availability. Additionally, Donega et al (2014), who evaluated containers and substrates for the production of seedlings and hydroponic cultivation of thyme (Thymus vulgaris L.), also observed a greater development when seedlings were produced in large-sized trays (32.61, 40 and 250 cm 3 ).…”
Section: Substratessupporting
confidence: 82%
See 1 more Smart Citation
“…Similar results were observed by Guimarães et al (2012), working with jurubeba (Solanum paniculatum) and cocona (Solanum sessiliflorum Dunal) seedlings, which observed with a higher length, fresh and dry shoot weight for seedlings grown in containers with a larger volume (32.61, 40 and 250 cm 3 ) and consequently with more substrate availability. Additionally, Donega et al (2014), who evaluated containers and substrates for the production of seedlings and hydroponic cultivation of thyme (Thymus vulgaris L.), also observed a greater development when seedlings were produced in large-sized trays (32.61, 40 and 250 cm 3 ).…”
Section: Substratessupporting
confidence: 82%
“…This process, while improving production efficiency, may also negatively affect the productivity of the species (Maggioni et al 2014). In general, research results have shown that larger containers provided better conditions for the seedlings to develop Costa et al 2011;Guimarães et al 2012). On the other hand, smaller cells result in substrate savings and in increased number of plants per area.…”
Section: Introductionmentioning
confidence: 99%
“…O melhor desempenho das mudas produzidas em recipientes de maior volume (162 células), também foi relatado por outros pesquisadores para diferentes espécies (Costa et al, 2011;Guimarães et al, 2012;Miqueloni et al, 2013;Lemos Neto et al, 2016). Segundo os pesquisadores, tais resultados podem ser explicados devido à maior quantidade de substrato disponibilizado para as plântulas em bandejas com maior volume de substrato (menor número de células).…”
Section: Resultsunclassified
“…Atualmente, são encontrados diferentes recipientes para a produção de mudas, todos com diferentes características como: número de células, profundidade, volume e formato (Guimarães & Feitosa, 2015). No entanto, das características citadas, o volume disponível no recipiente é a que mais impacta no crescimento e desenvolvimento inicial das mudas, como já demonstrado em diferentes trabalhos realizados (Costa et al, 2012;Guimarães et al, 2012;Lemos Neto et al, 2016;Mello et al, 2016).…”
Section: Introductionunclassified
“…Diante disso, o conhecimento da tecnologia de produção torna-se essencial (GUIMARÃES et al, 2012), sobretudo quanto às temperaturas (SANTOS et al, 2010), tamanho de recipientes e tipos de substratos mais adequados à espécie durante o estabelecimento das fases iniciais de crescimento (GUERRA et al, 2017). Esses fatores influenciam a velocidade e uniformidade da germinação das sementes (CARVALHO;NAKAGAWA, 2009), determinam o espaço disponível para o crescimento radicular (KANO et al, 2008) e atuam sobre a arquitetura das raízes e o estado nutricional das mudas (TESSARO et al, 2013), respectivamente.…”
Section: Introductionunclassified